COMMUNITY EDUCATION CAMPAIGN ON STUNTING PREVENTION THROUGH MILK CONSUMPTION IN KAMPUNG MEYES, NORTH MANOKWARI - Sientje Daisy Rumetor; Andoyo Supriyantono; Marlyn N. Lekitoo; Trisiwi W. Widayati; Evi Warintan Saragih; Bambang Tj Hariadi; Lukas Y. Sonbait; Diana Sawen (Jurnal Abdisci, 2026)
Background. Stunting is a chronic nutritional problem caused by prolonged inadequate nutrient intake, leading to impaired child growth where height falls below the age-standard. One effective intervention is dairy consumption, which provides protein, calcium, vitamin D, and other essential micronutrients. However, public awareness of its benefits is still limited, necessitating continuous education. Aims. To enhance public knowledge and awareness regarding stunting, its impact on child growth and development, and to promote the role of milk consumption as a nutritional intervention to support optimal growth and prevent stunting. Methods. This community service program (PKM) was carried out in Kampung Meyes, North Manokwari District, on May 12, 2025, involving 40 participants, including children and parents. The program used an educational campaign method through leaflet distribution, interactive discussions, and free milk distribution for children. The results showed a positive response: children were enthusiastic about milk consumption, community leaders expressed gratitude, and parents acknowledged the importance of nutrition education. Conclusion. Educational campaigns are effective in raising awareness and promoting behavioral change in the community. Regular follow-up programs and collaborative efforts among academics, local government, and the private sector are recommended to strengthen stunting prevention and improve child nutrition in rural communities.